Medicinal Plant Images - Cock1,2,*, Ian Edwin (Pharmacognosy Communications, 2026)
Syzygium leuhmannii (F.Muell.) L.A.S.Johnson (commonly known as riberry). Syzygium is a large genus of evergreen flowering plants of the family Myrtaceae which consists of approximately 500 species.8 Plants of this genus are widespread, occurring in tropical and subtropical regions of South-East Asia, Australia and Africa. Many Syzygium species produce edible fruits and berries. Some Syzygium spp. are used in traditional medicine to treat respiratory ailments, tuberculosis, gastro-intestinal disorders, diarrhoea and dysentery.1 Recent reports have also highlighted the Australian Syzygium species S. leuhmannii and Syzygium australe (Bush Cherry) extracts as having exceptionally high antioxidant contents.9 Antioxidants have been associated with the prevention of cancer, cardiovascular disease and neurological degenerative disorders.10-12 They are also linked with anti-diabetic bioactivities and have been associated with the reduction of obesity. Antioxidants can directly scavenge free radicals, protecting cells against oxidative stress related damage to proteins, lipids and nucleic acids.13 Thus, Syzygium spp. have potential in the treatment of a significant number of diseases and medical conditions related to cellular redox state.
Keywords: Medicinal Plant Images